Laboratory professionals" attitudes towards ISO 15189 2012 accreditation: an anonymous survey of three Croatian accredited medical laboratories - Lapić, Ivana (Array, 2021)
Effective implementation and continual compliance with ISO 15189:2012 require ongoing commitment and active involvement of laboratory staff. Our aim was to assess attitudes regarding accreditation implementation by conducting a survey in three Croatian accredited medical laboratories.An anonymous survey consisting of 34 questions was distributed either electronically or in a paper form a week prior to scheduled annual audits. Distributions of answers regarding age, work experience, laboratory workplace, and education level and according to the respective laboratory were compared.The overall response rate was 76% (225/297). Preference towards working in an accredited laboratory and a positive attitude were revealed by 70% and 56% participants, respectively, with better process documentation as the main advantage. Only 14% of responders considered themselves completely familiar with ISO 15189:2012. Total of 68% of responders felt that accreditation increases the usual workload, with excessive paperwork as the main contributor. Half of the responders declared partial agreement that accreditation requirements and expectations were clearly explained and claimed that their suggestions were taken into account only occasionally, which was especially emphasized by technical staff. The vast majority (89%) completely follow the prescribed protocols. Only 27% consider turnaround time monitoring useful. Competence assessment is considered efficient by 41% of responders. The majority (73%) prefer an online audit in times of COVID-19.Despite an overall positive attitude towards accreditation, further efforts are needed in providing better education about ISO 15189:2012 for technical staff and modifying formats of competence assessment, in order to achieve better adherence to ISO 15189:2012 requirements.